Immune system-mediated atherosclerosis caused by deficiency of long non-coding RNA MALAT1 in ApoE−/−mice - Gast, Martina; Haas, Jan; Meder, Benjamin (Cardiovascular research, 2019)
AbstractAims. The immune system is considered a key driver of atherosclerosis, and beyond proteins and microRNAs (miRs), long non-coding RNAs (lncRNAs) are imp